2018
DOI: 10.1038/s41408-018-0132-1
|View full text |Cite
|
Sign up to set email alerts
|

Differences in genomic abnormalities among African individuals with monoclonal gammopathies using calculated ancestry

Abstract: Multiple myeloma (MM) is two- to three-fold more common in African Americans (AAs) compared to European Americans (EAs). This striking disparity, one of the highest of any cancer, may be due to underlying genetic predisposition between these groups. There are multiple unique cytogenetic subtypes of MM, and it is likely that the disparity is associated with only certain subtypes. Previous efforts to understand this disparity have relied on self-reported race rather than genetic ancestry, which may result in bia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
43
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

4
3

Authors

Journals

citations
Cited by 53 publications
(48 citation statements)
references
References 28 publications
5
43
0
Order By: Relevance
“…11 In addition, estrogen could decrease myeloma tumor growth by inhibiting interleukin 6 via the PIAS3-STAT3 pathway. 3,14,15 The difference in results could be explained by health care disparities and socioeconomic differences between races. However, some previous studies have demonstrated that African American individuals had a 1.3-fold to 2-fold higher mortality risk compared with white individuals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…11 In addition, estrogen could decrease myeloma tumor growth by inhibiting interleukin 6 via the PIAS3-STAT3 pathway. 3,14,15 The difference in results could be explained by health care disparities and socioeconomic differences between races. However, some previous studies have demonstrated that African American individuals had a 1.3-fold to 2-fold higher mortality risk compared with white individuals.…”
Section: Discussionmentioning
confidence: 99%
“…However, some previous studies have demonstrated that African American individuals had a 1.3-fold to 2-fold higher mortality risk compared with white individuals. 3,14,15 The difference in results could be explained by health care disparities and socioeconomic differences between races. [16][17][18] After statistical adjustment of other sociodemographic factors in the current study, race was no longer found to be a significant prognostic factor, a finding that is consistent with the results of a previous population-based study.…”
Section: Discussionmentioning
confidence: 99%
“…Many previous studies evaluating the mechanism of racial disparities in MGUS/MM have assessed race using self-reported demographic data rather than utilizing ancestry informative single-nucleotide polymorphisms (SNPs) as a method to determine the proportion of racial admixture. Using SNP data, we have recently identified a higher prevalence of IgH translocations t (11;14), t(14;16) and t(14;20) in individuals with ≥80% African ancestry 11 . Enrichment of t (11;14) was confirmed in a more recent study 12 .…”
Section: Dear Editormentioning
confidence: 99%
“…Enrichment of t (11;14) was confirmed in a more recent study 12 . As an extension to our previous work 11 , we investigated which, if any, of the germline risk alleles previously associated with MM or MGUS risk, survival or risk of development of t(11;14) 13 (Supplemental Table 1) are enriched in individuals of African ancestry in our cohort of patients with plasma cell dyscrasias.…”
Section: Dear Editormentioning
confidence: 99%
“…This criterion is believed to account for the participants genetic background and supposedly allow controlling for population genetic structure (e.g. Baughn et al, 2018Baughn et al, , 2020. A numerical example of how a false positive association can be created due to population stratification is shown in Table 1 (Hellwege et al, 2017).…”
Section: Population Diversitymentioning
confidence: 99%